Prevalence and correlates of excessive fatigue among Moroccan school adolescents: A cross-sectional study - Marouane Moustakbal; Souad B. Maataoui (AOSIS, 2023)
Excessive fatigue in adolescents is a growing concern as it impacts various aspects of their lives. Research on its prevalence and contributing factors in specific populations, especially in developing countries, is scarce. This study examines the prevalence of excessive fatigue among Moroccan adolescents and its association with demographic characteristics, parasomnias, depressive symptoms, and academic performance. In this cross‑sectional study, we assessed excessive fatigue among 800 Moroccan adolescents (aged 12‑20 years) in Settat province, using a comprehensive questionnaire including Pichot's Fatigue Scale (PFS), Patient Health Questionnaire 9 (PHQ‑9), parasomnia questionnaire, and demographic questionnaire. The primary outcome was excessive fatigue, while covariates included demographic factors, physical health, regular exercise, depressive symptoms, and specific parasomnias. Associations were analyzed using cross‑tabulation analysis, chi‑squared tests, and correlation analysis. Excessive fatigue was prevalent in 8.4% of participants. Female adolescents had significantly higher adjusted odds of experiencing excessive fatigue than male adolescents, with an adjusted odds ratio (AOR) of 3.07 [95% CI (1.48, 6.37), P=0.003]. Excessive fatigue was significantly associated with nightmares, sleep paralysis, and hypnagogic hallucinations. A strong positive linear correlation was observed between fatigue and depressive symptoms (r=0.746, P0.001). This study highlights the prevalence of excessive fatigue among Moroccan adolescents, emphasizing the importance of addressing gender‑specific issues, sleep habits, and mental health support. Further research is needed to understand the underlying mechanisms and explore the role of lifestyle and socio‑cultural contexts.